The Thickness and Volume of Young Basalts Within Mare Imbrium. Issue 2 (26th February 2018) - Chen, Yuan; Li, Chunlai; Ren, Xin; Liu, Jianjun; Wu, Yunzhao; Lu, Yu; Cai, Wei; Zhang, Xunyu
Abstract: Basaltic volcanism is one of the most important geologic processes of the Moon. Research on the thickness and volume of late‐stage basalts of Mare Imbrium helps better understand the source of lunar volcanism and eruption styles. Based on whether apparent flow fronts exist or not, the late‐stage basalts within Mare Imbrium were divided into two groups, namely, Upper Eratosthenian basalts (UEm) and Lower Eratosthenian basalts (LEm). Employing the topographic profile analysis method for UEm and the crater excavation technique for LEm, we studied the thickness and distribution of Eratosthenian basalts in Mare Imbrium. For the UEm units, their thicknesses were estimated to be ~16–34 (±2) m with several layers of individual lava (~8–13 m) inside. The estimated thickness of LEm units was ~14–45(±1) m, with a trend of reducing thickness from north to south. The measured thickness of late‐stage basalts around the Chang'E‐3 landing site (~37 ± 1 m) was quite close to the results acquired by the lunar penetrating radar carried on board the Yutu Rover (~35 m). The total volume of the late‐stage basalts in Mare Imbrium was calculated to be ~8, 671 (±320) km 3, which is 4 times lower than that of Schaber's estimation (~4 × 10 4  km 3 ). Our results indicate that the actual volume is much lower than previous estimates of the final stage of the late basaltic eruption of Mare Imbrium. Together, the area flux and transport distance of the lava flows gradually decreased with time. These results suggest that late‐stage volcanic evolution of the Moon might be revised. Plain Language Summary: The late stage younger than 3.1 Ga volcanism of the Moon deposited large areas of basalts in Mare Imbrium and Oceanus Procellarum. These basalts have different colors (dark and blue) compared to old basalts sampled by Apollo and Luna missions. In order to understand how these young basalts erupted in Mare Imbrium, we estimated their thickness and volume using multiple data. Using detailed visible and near‐infrared spectral data in combination with topographic information, we estimated the height of lava flows and the thickness of late‐stage rocks excavated by impact craters. Our results indicate that these young basalts have a thickness of tens of meters and a total volume of ~8, 671 (±320) km 3 . Both values are smaller than those of previous estimates, suggesting a smaller volcanic activity than previously thought. These results indicate that the magmatic activity gradually weakened in this region. Key Points: We studied the thickness and volume of young basalts in Mare Imbrium based on topographic and spectral evidence Our research suggests that both thicknesses and volumes are less than the estimates of previous studies